The prognosis of pain and function in people with hand and thumb base osteoarthritis: a systematic review - Victoria Jansen; Anna Selby; Suzanne Toft; Joanna Greenway; Michelle Marshall; Elaine Nicholls; Danielle A. van der Windt (Annals of Medicine)
Background This systematic review has summarized evidence regarding the course of hand pain, hand function, and prognostic factors that predict changes in symptoms in people with hand and thumb base osteoarthritis.Methods A systematic search of electronic databases was conducted for longitudinal studies on hand osteoarthritis. Two reviewers assessed eligibility quality appraisal, and extracted data on pain, function and prognostic factors. A narrative synthesis was undertaken, and the strength of the evidence was appraised using a modified Grading of Recommendations, Assessment, Development, and Evaluations approach.Results Of 9523 articles identified, 24 papers with 8,496 patients met the inclusion criteria. Twelve studies reported on the course of hand pain and 13 on hand function. 25–29% of participants reported worsening pain and 23–59% a deterioration in hand function over 10 years. There is moderate evidence that, on average, function and grip strength deteriorate over time with minimal changes in average hand pain. Twelve studies assessed the prognostic factors for hand OA. Moderate evidence suggests baseline pain and diabetes are associated with changes in hand function and pain; lower quality evidence for other health and psychological factors.Conclusions Over 10 years, there is, little change in hand pain, but some deterioration in hand function. Deterioration in hand pain and function is associated with diabetes and higher baseline pain severity. Further research is very likely to improve our understanding of prognostic factors for symptomatic progression in hand OA.